1994
DOI: 10.1002/ptr.2650080303
|View full text |Cite
|
Sign up to set email alerts
|

Screening of nine vasoactive medicinal plants for their possible calcium antagonistic activity. Strategy of selection and isolation for the active principles of Olea europaea and Peucedanum ostruthium

Abstract: Fourteen different extracts of nine vasoactive medicinal plants used in European and African phytotherapy and traditional medicine were pharmacologically tested for their possible calcium antagonistic mode of action. The criteria for the selection of plants were: use in traditional medicine in the treatment of cardiovascular diseases, 'nonspecific' spasmolytic activity (mode of action not known), natural compounds with structural similarities to already known 'calcium-antagonists' or calcium-antagonists that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 17 publications
(18 reference statements)
1
20
0
1
Order By: Relevance
“…Besides this Rauwald et al have found 3,4-dihydroxyphenylethanol, i.e., hydroxytyrosol, the esterifying alcoholic component of the iridoid glycoside oleuropein, exerting vasodilative effects on isolated aortic rings, which have been interpreted as possible calcium antagonistic effects (Rauwald et al, 1991(Rauwald et al, , 1994, which would be in very good agreement to our present data. However, other components, yet unknown, in the extract may also contribute to the effect.…”
Section: Discussionsupporting
confidence: 93%
“…Besides this Rauwald et al have found 3,4-dihydroxyphenylethanol, i.e., hydroxytyrosol, the esterifying alcoholic component of the iridoid glycoside oleuropein, exerting vasodilative effects on isolated aortic rings, which have been interpreted as possible calcium antagonistic effects (Rauwald et al, 1991(Rauwald et al, , 1994, which would be in very good agreement to our present data. However, other components, yet unknown, in the extract may also contribute to the effect.…”
Section: Discussionsupporting
confidence: 93%
“…Oleuropein was also shown to enhance nitric oxide production (Visioli et al, 1998b), whereas a direct calcium antagonistic activity was excluded. However, after bioassay directed fractionation, 3,4-dihydroxy-phenyl-ethanol, a degradation product of oleuropein, was shown to have such potential (Rauwald et al, 1994). Other ß-glucosidaseproduced metabolites of oleuropein and oleacin have been shown to inhibit the angiotensin converting enzyme (ACE) (Hansen et al, 1996).…”
Section: Acknowledgementmentioning
confidence: 98%
“…Other research groups have subsequently conducted similar screening programs using rat thoracic aortas, guinea pig ileum, mouse myocardial cells, rat pituitary cells or cultured cells (43)(44)(45)(46)(47). Among the compounds listed in a review article written by Vuorela et al (48), furanocoumarines, coumarins and some mono-and sesquiterpenoids occupy a preferred place.…”
Section: Methodsmentioning
confidence: 95%